Representasi Budaya Sunda dalam Film - Muhammad Rais Mumtaz; Dedeh Fardiah (UNISBA Press, 2024)
Abstract. Technological developments and film developments have made the messages in films more diverse. The film Before, Now and Then (Nana) tells the story of a woman named Raden Nana Sunani who had to live in an era where women were considered second-class society at that time. This film is set in the Land of Sunda, so it contains a lot of elements of Sundanese culture. This research focuses on the representation of Sundanese culture in the film Before, Now and Then (Nana). The focus of this research is the film Before, Now and Then (Nana) which is limited to scenes, visuals, meanings, symbols and signs throughout the film which contain elements of Sundanese culture. Sundanese culture will be limited to customs, social activities and works. This study uses qualitative methods with Roland Barthes's semiotic analysis approach. Taking the research object, namely Sundanese cultural films in the film Before, Now and Then (Nana) and the filmmakers involved in the film as subjects. Collecting data using the method of observation and documentation. Observations are made by observing each scene, and the signs in the film. Documentation comes from sources other than films such as the internet and literature. While testing the validity of the data will use the triangulation method. The results of this study indicate that there is a representation of Sundanese culture in the film Before, Now, and Then (Nana) in terms of denotation, connotation and myth. The representation of Sundanese culture can be seen from the clothing in the form of kebaya, the traditional game in the form of kakawihan's kaulinan entitled jaleleuja, and the art of tilu songs and taps. Abstrak. Perkembangan teknologi dan perkembangan film menjadikan pesan dalam film semakin beragam. Film Before, Now and Then (Nana) bercerita tentang kisah seorang wanita bernama Raden Nana Sunani yang harus hidup di zaman dimana wanita dianggap masyarakat kelas dua pada saat itu. Film ini berlatar di Tanah Sunda sehingga banyak sekali mengandung unsur budaya Sunda di dalamnya. Penelitian ini berfokus kepada representasi budaya Sunda dalam film Before, Now and Then (Nana). Fokus penelitian ini adalah film Before, Now and Then (Nana) yang dibatasi pada adegan, visual, makna, simbol dan tanda sepanjang film yang terdapat unsur budaya Sunda. Budaya Sunda akan dibatasi pada adat istiadat, aktivitas sosial, dan karya. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis semiotika Roland Barthes. Mengambil objek penelitian yakni film budaya Sunda dalam film Before, Now and Then (Nana) dan subjeknya adalah para sineas yang terlibat dalam film. Pengumpulan data dengan menggunakan metode observasi dan juga dokumentasi. Observasi dilakukan dengan cara mengamati setiap adegan, dan tanda dalam film. Dokumentasi berasal dari sumber lain di luar film seperti internet dan literatur. Sementara uji keabsahan data akan menggunakan metode triangulasi. Hasil penelitian ini menunjukan terdapat representasi budaya Sunda pada film Before, Now, and Then (Nana) ditinjau dari denotasi, konotasi, dan mitos. Representasi budaya Sunda dapat dilihat dari busana berupa kebaya, permainan tradisional berupa kaulinan kakawihan berjudul jaleleuja, dan kesenian yakni tembang dan ketuk tilu.